MANAGING ENGINEERING UNDERGRADUATES’ LANGUAGE ANXIETY: INSTRUCTOR ROLE IN ONLINE THREADED DISCUSSIONS - Indra Devi, S.; Subatira, B.; Noraini, H.; Bharanidharan, S. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
The advancement of communication technologies has revolutionized language classrooms via the instrumentality of computer networks and its text-based nature has brought about applications such as online threaded discussions. This paper firstly aims to determine whether the engineering undergraduates of Limited English Proficiency (LEP) are affected by the psychological aspects of language learning as well as explore how they interact in online threaded discussions. Besides, it also investigates the instructor’s point of view on instructor intervention in the activity. The Language Profile Forms and the focused group interviews indicate that they lack confidence and are affected by language anxiety. The postings of the 15 LEP undergraduates which were analyzed for emerging themes reveal that they mainly asked questions. Even though their discussions lacked substance and were akin to ‘educationally less valuable talk’ (ELVT), the activity has provided them with the motivation and autonomy to socialize and interact, thus reducing their anxiety. The instructor being the main content provider in the discussion has played an important role in facilitating and enhancing cognitive processing besides keeping the learners engaged.